Editor's Notes - Tumanut, Michael A. (Philippine Journal of Public Administration; Vol 64 No 2 (2020), 2022)
This year’s second issue features four articles (two original articles and two reflections) and a book review. This set highlights the importance of institutions and organizations in the areas of service provision and decision making. Three of the articles investigated selected services in the government’s portfolio against the backdrop of the COVID-19 pandemic.